Clinical impact of carbapenems in critically ill patients with valproic acid therapy: A propensity-matched analysis - Hsiao, Shu-Chen; Lai, Wei-Hung; Chen, I-Ling; Shih, Fu-Yuan (Frontiers in Neurology, 2023)
Background Valproic acid (VPA) is one of the most widely used broad-spectrum antiepileptic drugs, and carbapenems (CBPs) remain the drug of choice for severe infection caused by multidrug-resistant bacteria in critically ill patients. The interaction between VPA and CBPs can lead to a rapid depletion of serum VPA level. This may then cause status epilepticus (SE), which is associated with significant mortality. However, the prognostic impact of drug interactions in critically ill patients remains an under-investigated issue. Objective The aim of this study was to compare the prognosis of critically ill patients treated with VPA and concomitant CBPs or other broad-spectrum antibiotics. Methods Adult patients admitted to a medical center intensive care unit between January 2007 and December 2017 who concomitantly received VPA and antibiotics were enrolled. The risk of reduced VPA serum concentration, seizures and SE, mortality rate, length of hospital stay (LOS), and healthcare expenditure after concomitant administration were analyzed after propensity score matching. Results A total of 1,277 patients were included in the study, of whom 264 (20.7%) concomitantly received VPA and CBPs. After matching, the patients who received CBPs were associated with lower VPA serum concentration (15.8 vs. 60.8 mg/L; p < 0.0001), a higher risk of seizures (51.2 vs. 32.4%; adjusted odds ratio [aOR], 2.19; 95% CI, 1.48–3.24; p < 0.0001), higher risk of SE (13.6 vs. 4.7%; aOR, 3.20; 95% CI, 1.51–6.74; p = 0.0014), higher in-hospital mortality rate (33.8 vs. 24.9%; aOR, 1.57; 95% CI, 1.03–2.20; p = 0.036), longer LOS after concomitant therapy (41 vs. 30 days; p < 0.001), and increased healthcare expenditure (US$20,970 vs. US$12,848; p < 0.0001) than those who received other broad-spectrum antibiotics. Conclusion The administration of CBPs in epileptic patients under VPA therapy was associated with lower VAP serum concentration, a higher risk of seizures and SE, mortality, longer LOS, and significant utilization of healthcare resources. Healthcare professionals should pay attention to the concomitant use of VPA and CBPs when treating patients with epilepsy. Further studies are warranted to investigate the reason for the poor outcomes and whether avoiding the co-administration of VPA and CBP can improve the outcomes of epileptic patients.